Effect of Humidity and Temperature on Dissipation of Chlorpyrifos and Diazinon in Andic Soils, Cauca, Colombia - Perez, E.H.; Paez, M.I.; Figueroa, A. (Asian Journal of Chemistry, 2013)
The economic activity of a region depends on agriculture and livestock. This is characterized by having a potato growing (Solamumtuberosum Linneo) technique for high commercial production, which supplies the south-western Colombia. The andic soils have organic carbon content between 8.4 and 19.5 %, high humidity retention capacity, low temperatures. These soils are subjected to the application of high amounts of pesticides by farmers, being the most used chlorpyrifos and diazinon due to its control against potato weevil (Premnotrypesvorax, Coleoptera: Curculionidae) and foliage pests: flea (Epitrixspp, Coleoptera: Chrysomelidae) and Toston (Liriomyzaquadrata, Diptera: Agromyzidae), respectively. Incubating the soil with the pesticides and maintaining the containers at 278, 288 and 298 K and humidities of 0, 20, 40, 60 and 100 % with relation to the field humidity. t1/2 ranged from 86-122 days for chlorpyrifos and 42-53 days for diazinon regardless of the amount of CO present in the soil. In general, it is concluded that the optimal conditions for the degradation of chlorpyrifos and diazinon in these soils are between 100-80 % of humidity in field and a temperature below 283 K, that is to say that the humidity in this case is leading to a faster degradation of pesticides.